Penanaman Nilai-Nilai Karakter Melalui Pembelajaran Pendidikan Kewarganegaraan (PKn) Terhadap Siswa MTsN 11 Agam - Darna Erlinda (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Character cultivation is a very important task that must be carried out by teachers as educators. Currently, many students no longer have character because they are influenced by globalization. So character cultivation is very important in learning all subjects, especially in Civics Education (PKn) as a subject that teaches material directly about character. The aim of this research is to find out about character cultivation through civic education (PKn) learning for MTsN 11 Agam students. This research is field research using a descriptive qualitative approach method. The results of this research explain that the cultivation of character through civics education (PKn) learning for MTsN 11 Agam students is going well, as evidenced by the implementation of these character values by students, such as: honesty, discipline, patience, helping each other, respecting each other, and so forth. Therefore, it is hoped that teachers will always instill character values in students so that the character of MTsN 11 Agam students will increase.